The Growth Response of Toman Fish (Channa micropeltes Cuvier.) with Different Satisfaction Times - Helmizuryani Helmizuryani; Khusnul Khotimah; Meika Puspita Sari; Novi Antika Sari (Program Pascasarjana Universitas Sriwijaya, 2022)
The high price of toman fish (Channa micropeltes Cuvier.) in the market is one of the reasons for the need for toman fish farming activities. However, the expensive price of commercial feed causes the cost of cultivation to be high. Effective and efficient feeding can reduce feed costs. Satisfaction is done so that the stomach is emptied in an uncharacteristic time, so it is expected to increase the appetite of Toman Fish. This study aims to determine the effect of grazing time on the growth of toman fish. This research was conducted in the Wet Fisheries Laboratory, Faculty of Agriculture, Muhamadiyah University of Palembang. From September to November 2021. The research method used is an experimental trial with a Non-Factorial Complete Randomised Design. Treatment factors include P1 (No gratification/control), P2 (1 day fasting 4 days fed), P3 (1 day fasting 3 days fed), P4 (1 day fasting 2 days fed), and P5 (1 day fasting 1 day fed). The changes observed were weight growth, length growth, and survival rate (SR). The treatment of 1-day of fasting and 1 day fed to toman fish (Channa micropeltes Cuvier.) is the best treatment for length growth (3.35 cm), weight (11.06 grams), and survival (89%).